THE EFFECTS OF THERAPEUTIC PHYSICAL EXERCISE ON CHILD OBESITY - Cristuta Alina Mihaela (ALTIUS ACADEMY Foundation - Faculty of Physical Education and Sports, 2014)
Obesity represents a world health problem, confronted by both adults and children, caused by the invasion of unhealthy foods, but also by a lack of information regarding the long term negative effects of an unbalanced diet.The aim of this research is to prove the beneficial role the correctly and constantly performed therapeutic physical exercise plays in the prevention of child obesity, but also in the fight with unwanted weight, starting from knowing the children's growth and development particularities, the obesity incidence among them, and the long term negative effects this disease has on their health.This research tries to confirm whether by applying therapeutic physical exercises in children, one can see their positive effects on obesity, and whether by applying a well-structured physical exercise program, organized and applied with regularity, one can obtain a drop in the obese children's weight.The means, methods, and procedures that are encompassed in a well structured and individualized program, then applying it perseveringly, correctly, and continuously, lead to the diminishing and correcting of the existing symptoms, preventing the installment of other complications.After applying the prophylactic physiotherapy programs, we can improve the somatoscopic aspect of the individual, the proportionality becomes harmonious, and the body's ability to adapt to the effort is improved.